2001
DOI: 10.1046/j.1365-2478.2001.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Successive cracking steps of a limestone highlighted by ultrasonic wave propagation

Abstract: A number of laboratory tests (uniaxial, triaxial and hydrostatic) have been conducted on a dry porous limestone. A conceptual model is proposed to correlate deformation and damage fields (including acoustic emission activity) with the variation of ultrasonic velocities, quality factors and energies as measures of attenuation. This correlation is presented in a stress deviator versus confining pressure diagram. In this way, the successive steps occurring in the damage process of this rock are well described. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…This can be further confirmed from the near‐linear relationship between the ε NE AT and the ultrasonic wave amplitude above the CI (Figure b), coherent with the findings of Wulff et al (). This observation is consistent with the studies of Wulff et al (), Couvreur et al (), and Barnhoorn et al (), who found that the changes in ultrasonic signals can be an objective signature of onset (not a precursor) of microcracking in rocks where the damage is diffuse (randomly distributed) and small relative to the ultrasonic wavelength (identical to the scenario in the present study).…”
Section: Resultssupporting
confidence: 94%
“…This can be further confirmed from the near‐linear relationship between the ε NE AT and the ultrasonic wave amplitude above the CI (Figure b), coherent with the findings of Wulff et al (). This observation is consistent with the studies of Wulff et al (), Couvreur et al (), and Barnhoorn et al (), who found that the changes in ultrasonic signals can be an objective signature of onset (not a precursor) of microcracking in rocks where the damage is diffuse (randomly distributed) and small relative to the ultrasonic wavelength (identical to the scenario in the present study).…”
Section: Resultssupporting
confidence: 94%
“…The subsequent increase in attenuation in the inelastic regime observed here for all three studied rock types confirms the observation of Couvreur et al (2001) that an increase in attenuation can be attributed to the appearance of new brittle fractures. Here, we have shown consistently that a minimum in attenuation occurs at the onset of inelastic deformation.…”
Section: Discussionsupporting
confidence: 90%
“…The formation of new fractures beyond the elastic limit generally decreases the wave velocity (Hadley, 1976;Granryd et al 1983;Yukutake, 1989;Sayers, 2002a;Fortin et al, 2007;Eslami et al, 2010;Nicolas et al 2016Nicolas et al , 2017Bonnelye et al, 2017). However, the change in attenuation during the fracturing process beyond the elastic limit has not yet been investigated extensively (Couvreur et al, 2001;Goodfellow et al, 2015); it is the main objective of this study. In analogy to fracture closure, where attenuation generally decreases (Zhubayev et al, 2016), fracture formation should cause an increase in attenuation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between compressibility and chemical processes made in section 3 must therefore be taken into account while interpreting the present ultrasonic velocity measurements. Crack propagation may also lower elastic wave velocity [ Couvreur et al , 2001], and reactive surface areas lower grain contact stiffness [ Vanorio et al , 2010], which might also explain lower velocity measurements in samples saturated with reactive fluids (Figures 5a and 5b). …”
Section: Discussionmentioning
confidence: 99%